Brain tissue loss occurs after suppression of enhancement in patients with multiple sclerosis treated with autologous haematopoietic stem cell transplantation. Issue 4 (16th March 2004) - Inglese, M; Mancardi, G L; Pagani, E; Rocca, M A; Murialdo, A; Saccardi, R; Comi, G; Filippi, M
Abstract : To assess whether brain tissue loss occurs after profound and sustained suppression of magnetic resonance imaging (MRI) enhancement, we measured brain volume changes from 10 patients with rapidly evolving secondary progressive multiple sclerosis (MS) treated with autologous haematopoietic stem cell transplantation and followed up for 24 months. An average yearly decrease of brain volume of about 1.9% was observed despite only five enhancing lesions seen on triple dose follow up scans of two patients. This indicates that, in MS, progressive loss of tissue can occur independently of concomitant MRI-visible inflammation.